Peningkatan Kualitas Lingkungan Melalui Inovasi Alat Pembakaran Sampah Minim Asap di Desa Gundu – Gundu - Edi; Permana, Dian (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The community service activity in Gundu-Gundu Village was motivated by coastal environmental issues, such as waste accumulation, the absence of a final disposal site (TPA), and air pollution caused by open burning of waste. To address these challenges, the implementation team designed an innovation in the form of a low-smoke waste incinerator made from recycled materials. The stages of the activity included field surveys, tool design and fabrication, as well as participatory socialization and trials with the community. The results demonstrated that the device was effective in reducing waste volume and minimizing smoke emissions, thereby improving air quality and the cleanliness of the coastal environment. In addition, the community’s positive response reflected an increase in awareness and behavioral change toward more environmentally friendly waste management practices.